Mr. All-Around : the life of Tom Gola - Grzybowski, David, 1991- (Temple University Press, 2018)
"Recounts the life of Tom Gola, the only player to win the National Invitational Tournament (NIT), the NCAA Tournament, and an NBA championship. The biography includes Gola's playing career at La Salle College and in the NBA, his coaching career at La Salle, and his subsequent career in Philadelphia politics"--